THE ROLE OF FAMILY IN PREVENTING SOCIAL CONFLICT IN SOCIETY FROM ISLAMIC PERSPECTIVES - Rusli, Rusli (Hunafa: Jurnal Studia Islamika, 2020)
This paper deals with the role of family in preventing social conflict and tensions within community. It is argued that family plays a significant role in establishing norms and rules in preventing social conflict and tension in the community. And in Islam, family is described as a school that children can learn moral values from their parents. The cultivation and strengthening of character in family can be carried out in various ways. First, providing halal food to the children since there is correlation between the food consumed and character; second, teaching moral values to the children so that they know what is good or not good in life; third, instilling good character values ​​into children so that they become good generations in society. This character education by parents includes, first, education that provides knowledge about the importance of values ​​that prevent conflict and violence in society; second, education that provides good examples, and third, education through continuous habituation